Pengelolaan Perusahaan Berbasis âGood Corporate Governanceâ - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Bondan Wismandanikung (Teknis, 2015)
Good Corporate Governance (GCG) it is realy complicated for the company caused include of technical and non-technical aspects which is more tends weighted in non-technical aspect such as stake-holders whose involved to the company. The keys company to success are strategy, organization, human resources, leadership style, information system and consumers orientation would be describes as for achievement targets of the company.Â In the other side a company culture would be adopted as a valued system manual of performance members of company such as mutual trust, integrity, care and leaner should be known and done in order to get a better achievement of the company target. Here, we are try to describe the manual of Good Corporate GovernanceÂ in supporting succesfull of bisnisKeywords: ownership, management, members, stake holder, Good Corporate Governance.